The basic characteristics of extracellular vesicles and their potential application in bone sarcomas - Li, Shenglong (Journal of nanobiotechnology, 2021)
Bone sarcomas are rare cancers accompanied by metastatic disease, mainly including osteosarcoma, Ewing sarcoma and chondrosarcoma. Extracellular vesicles (EVs) are membrane vesicles released by cells in the extracellular matrix, which carry important signal molecules, can stably and widely present in various body fluids, such as plasma, saliva and scalp fluid, spinal cord, breast milk, and urine liquid. EVs can transport almost all types of biologically active molecules (DNA, mRNA, microRNA (miRNA), proteins, metabolites, and even pharmacological compounds). In this review, we summarized the basic biological characteristics of EVs and focused on their application in bone sarcomas. EVs can be use as biomarker vehicles for diagnosis and prognosis in bone sarcomas. The role of EVs in bone sarcoma has been analyzed point-by-point. In the microenvironment of bone sarcoma, bone sarcoma cells, mesenchymal stem cells, immune cells, fibroblasts, osteoclasts, osteoblasts, and endothelial cells coexist and interact with each other. EVs play an important role in the communication between cells. Based on multiple functions in bone sarcoma, this review provides new ideas for the discovery of new therapeutic targets and new diagnostic analysis.